2019
DOI: 10.3390/su11143836
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Environmental Impact Savings Potential through Innovative Biorefinery Alternatives: An Application of the TM-LCA Framework for Regional Scale Impact Assessment

Abstract: In order to compare the maximum potential environmental impact savings that may result from the implementation of innovative biorefinery alternatives at a regional scale, the Territorial Metabolism-Life Cycle Assessment (TM-LCA) framework is implemented. With the goal of examining environmental impacts arising from technology-to-region (territory) compatibility, the framework is applied to two biorefinery alternatives, treating a mixture of cow manure and grape marc. The biorefineries produce either biogas alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…Very recently, a review on the link between sustainability and industrial waste streams as feedstock for the production of PHAs has been published [44]; many different industrial streams have been taken into consideration, including activated sludge and industrial aqueous streams. The authors agree that the consideration of waste stream exploitation as a bacteria growth substrate is an interesting contribution towards a circular bioeconomy [44], economic competitiveness against fossil-based products [34,42], and eco-sustainability [43,45]. However, there is also a general agreement on the need for further investigations in order to improve the PHAs production process [40,44,46,47], and to deeply explore the environmental performances [41], thus avoiding possible burden shifting [43] and widening the analysis to include disregarded impacts like water use, land use, and eutrophication [39].…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Very recently, a review on the link between sustainability and industrial waste streams as feedstock for the production of PHAs has been published [44]; many different industrial streams have been taken into consideration, including activated sludge and industrial aqueous streams. The authors agree that the consideration of waste stream exploitation as a bacteria growth substrate is an interesting contribution towards a circular bioeconomy [44], economic competitiveness against fossil-based products [34,42], and eco-sustainability [43,45]. However, there is also a general agreement on the need for further investigations in order to improve the PHAs production process [40,44,46,47], and to deeply explore the environmental performances [41], thus avoiding possible burden shifting [43] and widening the analysis to include disregarded impacts like water use, land use, and eutrophication [39].…”
Section: Introductionmentioning
confidence: 86%
“…The authors agree that the consideration of waste stream exploitation as a bacteria growth substrate is an interesting contribution towards a circular bioeconomy [44], economic competitiveness against fossil-based products [34,42], and eco-sustainability [43,45]. However, there is also a general agreement on the need for further investigations in order to improve the PHAs production process [40,44,46,47], and to deeply explore the environmental performances [41], thus avoiding possible burden shifting [43] and widening the analysis to include disregarded impacts like water use, land use, and eutrophication [39]. The reviews of Narodoslawsky and co-authors [48] and Cristóbal and co-authors [49] show a great variability among the LCA results obtained by the different authors due to technological differences but also different choices in the LCA applications.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…This is due to the feedstock mix emissions in Bavaria, which are no longer counterbalanced by high emissions savings from offsetting of electricity. As has been shown before [26,84], offsets from replacing GHG intensive sources of electricity production such as coal, diminish as 'green' energy sources are implemented in the energy grid. The implications of this are very important for technologies producing renewable fuels, as their potential to produce savings will be bound to this future component.…”
Section: Sensitivitymentioning
confidence: 99%
“…An inadequate assessment of a plant's sourcing ability may lead to high operation costs from increased transport demand or inadequate sourcing of feedstock [25]. In turn, high transport distances may negate the environmental benefits brought about by biorefineries, as shown in Croxatto Vega et al [26] which applied the territorial metabolism-LCA approach (TM-LCA) [27] and found distances of 50 km to be the upper limit.…”
Section: Introductionmentioning
confidence: 99%